Acute effects of the ACE inhibitor enalaprilat on the pulmonary, cerebral and systemic blood flow and resistance after the bidirectional cavopulmonary connection. Issue 16 (5th June 2011) - Lee, Kyong-Jin; Yoo, Shi-Joon; Holtby, Helen; Grant, Brian; Mroczek, Dariusz; Wong, Derek; Grosse-Wortmann, Lars; Benson, Leland N; Chaturvedi, Rajiv R
Abstract : Background: The bidirectional cavopulmonary connection (BCPC) is used in the staged palliation of univentricular hearts and places the cerebral and pulmonary vascular beds in series. Angiotensin-converting enzyme inhibitors (ACEI) are often used in this complex circulation, but the effects of their vasodilation are unclear. Objective: Assessment of the acute response of perfusion pressure, flow and resistance across the systemic, cerebral and pulmonary vascular beds to ACEI in patients with a BCPC. Design: Prospective interventional study. Setting: Single tertiary care centre. Patients: 12 patients with a BCPC (median age 28 months, weight 11.8 kg) undergoing a pre-Fontan catheterisation with MRI measurement of flows. Intervention: Intravenous enalaprilat 0.005 or 0.01 mg/kg. Results: Enalaprilat increased descending aorta flow (median 21.6%, p=0.0005), decreased total pulmonary vein flow (median 10.6%, p=0.025), and both superior caval vein flow (median 8.6%, p=0.065) and aortopulmonary collateral flow (median 15.5%, p=0.077) tended to decrease. Total cardiac output was unchanged (p=0.57). Systemic vascular resistance (median 41.9%, p=0.0005) and cerebral vascular resistance (median 23.4%, p=0.0005) decreased, but pulmonary vascular resistance (p=0.73) showed little change. There was evidence of autoregulation of cerebral blood flow. The proportion of descending aortic flow to total cardiac output increased (median 27 to 35%, p=0.001). Systemic oxygen saturation decreased from 87% to 83% (p=0.02). Conclusion: Enalaprilat did not increase total cardiac output but redistributed flow to the lower body, with a concomitant decrease in arterial oxygen saturation. It is difficult to increase cardiac output in patients with a BCPC and ACEI should be used with caution in those with borderline aortic saturations.